DEGRO practical guideline for central nervous system radiation necrosis part 2: treatment - Bernhardt, Denise; Koenig, Laila; Grosu, Anca-Ligia; Rieken, Stefan; Krieg, Sandro M.; Wick, Wolfgang; Wiestler, Benedikt; Schmidt-Graf, Friederike; Sahm, Felix; Gempt, Jens; Meyer, Bernhard; Krause, Bernd J.; et al. (Strahlentherapie und Onkologie, 2022)
Purpose The Working Group for Neurooncology of the German Society for Radiation Oncology (DEGRO; AG NRO) in cooperation with members of the Neurooncological Working Group of the German Cancer Society (DKG-NOA) aimed to define a practical guideline for the diagnosis and treatment of radiation-induced necrosis (RN) of the central nervous system (CNS). Methods Panel members of the DEGRO working group invited experts, participated in a series of conferences, supplemented their clinical experience, performed a literature review, and formulated recommendations for medical treatment of RN, including bevacizumab, in clinical routine. Conclusion Diagnosis and treatment of RN requires multidisciplinary structures of care and defined processes. Diagnosis has to be made on an interdisciplinary level with the joint knowledge of a neuroradiologist, radiation oncologist, neurosurgeon, neuropathologist, and neurooncologist. If the diagnosis of blood-brain barrier disruptions (BBD) or RN is likely, treatment should be initiated depending on the symptoms, location, and dynamic of the lesion. Multiple treatment options are available (such as observation, surgery, steroids, and bevacizumab) and the optimal approach should be discussed in an interdisciplinary setting. In this practice guideline, we offer detailed treatment strategies for various scenarios.
CRIS-Team WoS Importer:2022-09-09